The potency of Micrococcus sp. L II 61 bacteria as oil sludge cleaning agent - Ni’matuzahroh Ni’matuzahroh; Intan Ayu Pratiwi; Tini Surtiningsih; Fatimah Fatimah; Sri Sumarsih (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2017)
This research aimed to reveal the ability of Micrococcus sp. L II 61 bacteria that was isolated from Pegirian Surabaya as oil cleaning agent. This is an experimental research to detect the presence of biosurfactant and lipase enzyme in culture supernatant of Micrococcus sp. L II 61 with aliphatic hy-drocarbon (cooking oil) as a substrate growth. Biosurfactant production was evaluated by measuring the surface tension of supernatant using tensiom-eter du Nouy and measuring the emulsification activity value using diesel oil as hydrocarbon test. Lipase enzyme was detected by measuring lipolitic activity value of crude enzyme (culture supernatant) by using p-nitrofenil palmitic (p-npp) as a substrate test. Data were analyzed descriptively. The results showed that Micrococcus sp. L II 61 produced biosurfactant with surface tension decreasing of culture supernatant up to 30.27 ± 1.17 mN/m compared than aquadest and value of hydrocarbon emulsification activity (AE 1 hour) up to 20.24 ± 0.68 %. Culture of Micrococcus sp. L II 61 after 16 hours incubation have a lipolytic activity 33.53 ± 0.14 U/mL at pH 7 and 37 oC. Supernatant of Micrococcus sp. L II 61 100% (v/v) give the high-est percentage of oil sludge solubility, i.e. 86.38 ± 2.39%. Micrococcus sp. L II 61 is a highly potential to be developed as oil sludge cleaning agent.